PENCIPTAAN KARYA-KARYA SENI CETAK SARING DENGAN OBJEK VISUAL YANG BERBASIS KEARIFAN LOKAL - Adi, sigit Purnomo; Sukerta, Pande Made; Marianto, Martinus Dwi; Hadi, Sri (Acintya, 2021)
Sablon or screen printing has many functions and is usually more popular in the community for making t-shirts and banners and even batik cloth. The popularity of screen printing or screen printing, which is used by world-class artists, one of them Andy Warhol and also used by Marida Nasution, causes writers to feel inspired to work using this technique, because the technique is already popular in the community, making it easy to get tools and materials. To visualize this work, the author uses an art creation research methodology with an artistic creation process. The artistic creation process requires several stages to be passed, including experimentation, reflection and finally formation. The selection of these objects is indeed very interesting because these objects are increasingly disappearing in our lives. So that in this work, we try to marry or collaborate between modern art represented by graphic art with visual objects based on local wisdom that represent tradition. The paradigm of modern art with a touch of tradition as an effort to find the roots of the characteristics of Indonesia from year to year has begun to be explored by artists in Indonesia as an effort to find Indonesian cultural identity.Keyword: Sablon, Artistic Creative, Printmaking.